Bleeding Scales Applicable to Critically Ill Children: A Systematic Review. Issue 7 (July 2019) - Nellis, Marianne E.; Levasseur, Julie; Stribling, Judy; Faustino, E. Vincent S.; Zantek, Nicole D.; Sheth, Sujit; Karam, Oliver
Abstract : Objectives: To summarize current bleeding scales and their validation to assess applicability to bleeding in critically ill children. Data Sources: We conducted electronic searches of Ovid MEDLINE, Ovid EMBASE, Cochrane Library, and Web of Science Core Collection databases from database inception to 2017. Study Selection: Included studies contained a bleeding score, bleeding measurement tool, or clinical measurement of hemorrhage. Data Extraction: We identified 2, 097 unique citations; 20 full-text articles were included in the final review. Data Synthesis: Of the 18 studies that included subjects (two others were expert consensus definitions), seven (39%) were pediatric-only, seven (39%) were adult-only, and four (22%) included both adults and children. Nine (50%) occurred with inpatients (two studies in critical care units), seven (39%) involved outpatients and two (11%) included both inpatients and outpatients. Thirty-nine percent of the scales were developed for those with idiopathic thrombocytopenic purpura and only two (12%) described critically ill patients. The majority (80%) included need for treatment (either RBC transfusion or surgical intervention). The majority (65%) did not report measures of reliability or validation to clinical outcomes. Conclusions: There is a lack of validated bleeding scales to adequately assess bleeding and outcomes in critically ill children. Validated scales of bleeding are necessary and urgently needed. Abstract : Supplemental Digital Content is available in the text.